OPERATIONAL CAPACITY PLANNING AND EFFECTIVENESS OF MORTGAGE BANKS IN RIVERS STATE, NIGERIA (American Journal of Research in Humanities and Social Sciences, 2025)
This study examined operational capacity planning and effectiveness of mortgage banks in Rivers State, Nigeria. This study was guided by two measures of operational capacity planning namely capacity scheduling and capacity utilization, together with two indicators of effectiveness like adaptability and cost reduction. The researcher applied survey design purposive sampling method useful in collection of data. The population size for this study was 150 employees carefully chosen from five mortgage banks in Rivers State, Nigeria. Managers and supervisors were the selected participants. A sample size of 109 employees was unveiled through the aid of Taro Yamane’s formula. Structured questionnaire was used as the primary research instrument while information received from Rivers State government statistics and mortgage bank reports served as the secondary source. Spearman correlation coefficient was used to test the hypotheses. The findings of the study indicated that there was a positive significant relationship between capacity scheduling and adaptability, together with capacity utilization has positive relationship with cost reduction. The researcher insisted that operational capacity planning is positively connected to effectiveness of mortgage banks in Rivers State, Nigeria. The researcher recommended that mortgage banks should implement effective capacity utilization that could minimize production cost.